Uji Aktivitas Fraksi Etil Asetat Daun Kopi Robusta terhadap Penurunan Kadar Glukosa Darah pada Mencit yang Diinduksi Streptozotosin - Aulia Zainul Ilmi (Fakultas Farmasi, 2026)
Diabetes mellitus is a chronic metabolic disorder characterized by persistent hyperglycemia and requires long-term therapy. The use of synthetic antidiabetic drugs still presents several limitations, including relatively high treatment costs and the need for prolonged use, thus encouraging the exploration of alternative therapies derived from natural products. Robusta coffee (Coffea canephora) leaves are known to contain various secondary metabolites with potential antidiabetic activity; however, studies focusing on specific fractions are still limited. This study aimed to evaluate the effect of the ethyl acetate fraction of robusta coffee leaves on blood glucose reduction, determine the optimal dose, and identify potential antidiabetic compounds. This research employed a laboratory experimental design with a pretest–posttest control group using streptozotocin-induced male mice. The animals were divided into six groups: normal control, negative control, positive control (glibenclamide), and three treatment groups receiving ethyl acetate fraction at doses of 100, 200, and 400 mg/kgBW for 14 days. Blood glucose levels were measured before and after treatment and analyzed using the Kruskal–Wallis test followed by the Mann–Whitney test. Compound identification was conducted using LC-MS, followed by in silico analysis through molecular docking. The results showed that doses of 100 and 200 mg/kgBW significantly reduced blood glucose levels compared to the negative control, with the greatest reduction observed at 200 mg/kgBW, exceeding the effect of glibenclamide. In contrast, the 400 mg/kgBW dose increased blood glucose levels. LC-MS analysis identified 27 compounds, of which seven were selected for molecular docking analysis. The results revealed that three compounds exhibited good binding affinity toward the target proteins.
FINALISASI oleh Arif 2026 Juli 10
Keywords: diabetes mellitus; Coffea canephora leaves; ethyl acetate fraction; blood glucose; molecular docking